Studies on Schismatoglottideae ( Araceae ) of Borneo XXXIV — Schismatoglottis iliata , a new species from NW Sarawak, and notes on the Schismatoglottis Multiflora Group and the Schismatoglottis mayoana Complex - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2014)
A summary of the Schismatoglottis Multiflora Group of Hay & Yuzammi is presented and the group shown to comprise about 15 species, including that described here. Schismatoglottis iliata P. C. Boyce & S. Y. Wong is described as a taxonomic novelty from forested sandstone riverside bluffs of the Ulu Batang Kayan, Lundu District, Kuching Division, NW Sarawak, Malaysian Borneo, and compared with the morphologically most similar species, S. mayoana Bogner & M. Hotta and S. nicolsonii A. Hay, with which S. iliata shares leaf blades adaxially matt olive green and abaxially with very fine and dense (c. 2 veins per mm) pellucid secondary venation, and stamen thecae each with two pores. A key to this newly recognized S. mayoana Complex is provided, and all described species for the S. mayoana Complex are illustrated.